The Effect of the COVID-19 Pandemic on the Mental Health of Healthcare Providers (HCPs) for Patients with Confirmed or Suspected Cases of COVID-19 - Al Buniaian, Nada; Al-Olimat, Hmoud; Abu Ghaboush, Reham; Alajmi, Abduruhman; Alqdah, Talal (Dirasat: Human and Social Sciences, 2022)
The healthcare providers who actively participated in the COVID-19 pandemic were more likely to experience mental health problems. This cross-sectional study sought to understand the effect of the COVID-19 pandemic on healthcare providers’ mental health. It evaluated a sample of 220 out of 2000 who participated in the Saudi Arabia Eastern Province pandemic. Tylor scale was used to analyze the anxiety levels, where the independent variables included age, gender, job type, job nature, and faith degree (religious commitment). The results indicated a significant relationship between the independent variables analyzed. The Tylor scale showed that (34.55%) of the participants had middle anxiety levels, and (11.81%) of the participants had high anxiety levels. The study also found that other sample characteristics do not correlate with TMAS levels. This study provides information that may help mitigate the effects of COVID-19 in the healthcare system. Practical solutions, including education and policy reformulations, may be incorporated into addressing healthcare providers’ mental health needs and challenges.